(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
While the study Female Print and the Culture of Femininity, Женска штампа и култура женствености, published 25 years ago, determined that the printing of heart is the medium of the culture of femininity, which supports the traditional perception of women and female nature, contemporary insights into the themes of this print reveal its emphasized orientation towards consumption as the main theme, and the heroine of this consumption – the shopaholic. Today, in Serbia, two types of print for women are dominant: luxurious, licensed, relatively expensive, low circulation glossy magazines with content dominated by His Majesty the Advertisement, and cheap, popular, sometimes licensed print for women with dominant content of practical and advisory orientation. The increasingly scarce local and traditional woman’s magazines of general type are surviving the competition with difficulty.